Taccalonolides: Structure, semi-synthesis, and biological activity - Li, Yan; Du, Yu-Feng; Gao, Feng; Xu, Jin-Bu; Zheng, Ling-Li; Liu, Gang; Lei, Yu (Frontiers in Pharmacology, 2022)
Microtubules are the fundamental part of the cell cytoskeleton intimately involving in cell proliferation and are superb targets in clinical cancer therapy today. Microtubule stabilizers have become one of the effectively main agents in the last decades for the treatment of diverse cancers. Taccalonolides, the highly oxygenated pentacyclic steroids isolated from the genus of Tacca, are considered a class of novel microtubule-stabilizing agents. Taccalonolides not only possess a similar microtubule-stabilizing activity as the famous drug paclitaxel but also reverse the multi-drug resistance of paclitaxel and epothilone in cellular and animal models. Taccalonolides have captured numerous attention in the field of medicinal chemistry due to their variety of structures, unique mechanism of action, and low toxicity. This review focuses on the structural diversity, semi-synthesis, modification, and pharmacological activities of taccalonolides, providing bright thoughts for the discovery of microtubule-stabilizing drugs.